2016
DOI: 10.1016/j.ultsonch.2016.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Intensified depolymerization of aqueous polyacrylamide solution using combined processes based on hydrodynamic cavitation, ozone, ultraviolet light and hydrogen peroxide

Abstract: The present work deals with intensification of depolymerization of polyacrylamide (PAM) solution using hydrodynamic cavitation (HC) reactors based on a combination with hydrogen peroxide (H2O2), ozone (O3) and ultraviolet (UV) irradiation. Effect of inlet pressure in hydrodynamic cavitation reactor and power dissipation in the case of UV irradiation on the extent of viscosity reduction has been investigated. The combined approaches such as HC+UV, HC+O3, HC+H2O2, UV+H2O2 and UV+O3 have been subsequently investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…122 The ozone molecule is extremely unstable in the presence of UV, releasing oxygen and forming hydrogen peroxide after reaction with water. 123 Ozone degrades PAM via free radical induced chain scission as described previously. 123 Ozonation at a concentration of 3.0 mg/L (w/v) leads to an 80% reduction in the MW of PAM within 15 min at pH 3.…”
Section: Fig 3 Hydrolysis Of Pam Generating a Carboxylic Acid Group mentioning
confidence: 99%
See 1 more Smart Citation
“…122 The ozone molecule is extremely unstable in the presence of UV, releasing oxygen and forming hydrogen peroxide after reaction with water. 123 Ozone degrades PAM via free radical induced chain scission as described previously. 123 Ozonation at a concentration of 3.0 mg/L (w/v) leads to an 80% reduction in the MW of PAM within 15 min at pH 3.…”
Section: Fig 3 Hydrolysis Of Pam Generating a Carboxylic Acid Group mentioning
confidence: 99%
“…123 Ozone degrades PAM via free radical induced chain scission as described previously. 123 Ozonation at a concentration of 3.0 mg/L (w/v) leads to an 80% reduction in the MW of PAM within 15 min at pH 3. Suziki et al 117 also demonstrated that acrylamide monomer could be almost completely degraded after 30 min of exposure to ozone at pH 6.…”
Section: Fig 3 Hydrolysis Of Pam Generating a Carboxylic Acid Group mentioning
confidence: 99%
“…The biological activities of chitosan, including anticancer, antimicrobial and scavenging reactive oxygen species, were influenced by the degree of deacetylation (DDA) and MM of chitosan (Czechwska-Biskup et al, 2012;Pastor et al, 2013). To improve its solubility and biological properties, several methods including chemical (oxidative and acidic degradation) (Tsao et al, 2011;Prajapat & Gogate, 2016a), physical (irradiation treatment) (Yue et al, 2009;Fiamingo et al, 2016;Prajapat & Gogate, 2016b) and enzymatic treatment (Mengibar et al, 2011) were employed to prepare low MM of chitosan with high DDA without altering its chemical structure. The physical methods used alone had many drawbacks such as an expensive apparatus, irregular degradation rate and long reaction time.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, cavitation results in sonophysical effects such as shear forces, velocity gradients, microstreaming, micro-jets and shock waves. [17][18][19] The first effect of applying US to polymer solutions (sonication) is polymer degradation (polymer-chain scission). Solvodynamic forces resulting from the cavitation cause the polymer chain to become divided and the molecular weight to decrease.…”
Section: Introductionmentioning
confidence: 99%